9 - Amadou-Mahtar M’Bow: Humanist - Amy Niang, (CODESRIA Bulletin, 2025)
Amadou-Mahtar M’Bow passed away at the age of 103, leaving behind a legacy deﬁned by his desire for a just and equitable world. He will be remembered for his commitments to knowledge and multilateralism, and to diplomacy as both a condition of freedom and a necessary instrument of a better future. First as Minister of Education in Sen- egal and then as Director-General of UNESCO, M’Bow championed causes and laid agendas for the twentieth century. These included the necessity for human connection through access to the means of information and related technologies; the relatability of the universal to the collective human heritage; and the restitution to Africa of its history and its recognition as an essential component of the human trajectory. Underneath it all, M’Bow had an unwavering attachment to a humanistic ethos of solicitousness, engagement, inclusion and respect for the other.